Quadruple Fixed Point Theorems under Nonlinear Contractive Conditions in Partially Ordered Metric Spaces. (5th July 2012) - Karapınar, Erdal; Shatanawi, Wasfi; Mustafa, Zead
Abstract : We prove a number of quadruple fixed point theorems underϕ -contractive conditions for a mappingF : X 4 → X in ordered metric spaces. Also, we introduce an example to illustrate the effectiveness of our results.